2015
DOI: 10.33225/jbse/15.14.85
|View full text |Cite
|
Sign up to set email alerts
|

Bitara-Stemtm Training of Trainers’ Programme: Impact on Trainers’ Knowledge, Beliefs, Attitudes and Efficacy Towards Integrated Stem Teaching

Abstract: The Bitara-STEMTM Training of Trainer Programme is a short-term professional development programme aimed to increase STEM teachers or facilitators’ abilities to teach integrated STEM education and to increase their efficacy, beliefs and attitudes of integrated STEM teaching. The programme involves 35 facilitators, representing a broad spectrum of STEM fields. Pre- and post-test results of the participants’ beliefs, attitudes, perceived efficacy and content knowledge in the context of integrated STEM teaching r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…As a result, instructors should be exposed to professional development programs that will improve their expertise on a regular basis. The results of the present study are consistent with previous study of Shahali et al (2015) on improving participants STEM knowledge. This previous study found significantly higher scores for participants' scores on the STEM knowledge content.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, instructors should be exposed to professional development programs that will improve their expertise on a regular basis. The results of the present study are consistent with previous study of Shahali et al (2015) on improving participants STEM knowledge. This previous study found significantly higher scores for participants' scores on the STEM knowledge content.…”
Section: Discussionsupporting
confidence: 93%
“…These necessitated researchers to recommend SPDP as a way out of the disheartening situation and researchers have shown it to improve researchers STEM knowledge over the years. Shahali et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Positive STEM educator viewpoints will influence classroom teaching strategies and contribute to learner perceptions by modeling interactions. Researchers (Aslam et al, 2018;Watermayer & Montgomery, 2018) discovered that teachers serve as the primary gatekeepers for the implementation of STEM in many countries worldwide (Carpenter & Lubinski, 1990;Relich et al, 1994;Shahali et al, 2015). As a result, the STEM self-efficacy for stimulated strategies, demonstrating positive interaction between teachers and students, highlighting the scholars' arguments, and reaching a substantial difference called out the learning effect was better than before the activity.…”
Section: T-test For the Pbl-stem Self-efficacy For Stimulated Strategymentioning
confidence: 99%
“…In terms of external performance, the post-test results of the PBL-STEM cake-baking experiential activities in terms of external efficacy are better than those of the pre-test, and there is a discernible improvement. Shahali et al (2015) pointed out that STEM educator attitudes influence learners, making students feel pressure to finish and do well on learning activities and making them want to give up when they haven't. They also find practical STEM cake-baking technology courses, which are simpler to understand and similar to Kassaee & Rowell's (2016) research, echoing the claim that STEM education belongs to real-world experience.…”
Section: T-test For the Pbl-stem Self-efficacy For Stimulated Strategymentioning
confidence: 99%
See 1 more Smart Citation